Towards a greater global understanding of what mediators do - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2012)
In this post on the Kluwer Mediation Blog, the western facilitative mediation approach in relation to historical and cross-cultural perspectives is discussed.